A Study on Socio-demographic Profile and Outcome of Tuberculosis in HIV-TB Co-infected Cases in Surat City, Western India - Vaibhav Gharat; Bhautik P Modi; Prakash Patel; Sunil Nayak; Ajay Pawar; R K Bansal (Medsci Publications, 2017)
Background: As tuberculosis is one of the most common causes of morbidity and mortality in HIV-infected individuals. The present study was planned with an objective to find out the socio-demographic profile of HIV-Tb co-infected cases. Methodology: This was a descriptive longitudinal study of HIV TB co-infected patients registered in Revised National Tuberculosis Control Programme (RNTCP) and Anti-retroviral Therapy (ART) centre. Results: Diagnosis of both HIV and tuberculosis at the same time was positive in 104 (51.0%) of the patients. Majority (77.0%) of the cases were having extra-pulmonary tuberculosis which includes abdominal, lymph node, inguinal nodes, etc. Sputum positivity was seen in 22 (34.4%) of the cases. Radiological findings were significant in 24.5% of the cases HIV Tb co-infected cases. It was found 146 (75.6%) of the cases had favourable outcome i.e., cure and treatment completed. Conclusion: It was observed that 75.6% of the cases of the HIV-TB co-infected cases had a favourable outcome (cured and treatment completed). Active case finding of Tuberculosis should be done in HIV cases as we observed 51% cases having TB and HIV diagnosed simultaneously.